Criteria for Selecting of German Economic Texts for the Aims of Foreign Language Teaching for Specific Purposes (UNWE Yearbook, 2017)
Focusing on the topic of the specific features of economic texts, the article presents a descriptive textlinguistic model which can be applied to  their analysis. On the basis of their textlinguistic features, the author offers a number of tasks so as the selected texts can be employed in a consistent practice aimed at the development of reading and summarizing skills of students at the CEFR levels when teaching German for Specific Purposes.